2020
DOI: 10.1108/ijsi-05-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

State of the art on geopolymer concrete

Abstract: PurposeImportant differentiating attributes in the procedures used, the characteristic mineral composition of the binders, and the implications these have on the final long term stability and physico-mechanical performance of the concretes produced are identified and discussed, with the intent to improve transparency and clarity in the field of geopolymer concrete technologies.Design/methodology/approachThis state-of-the-art review covers the area of geopolymer concrete, a class of sustainable construction mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A geopolymeric product formation can be done by evaluating the operational envelope for synthesizing the geopolymers, i.e., by evaluating the ternary diagram of SiO 2 , Na 2 O, and Al 2 O 3 (Fig. 5a), it was observed that all the samples produced in the present work were contained in the envelope synthesis of geopolymer described in the literature [46,47]. Fig.…”
Section: Resultsmentioning
confidence: 80%
“…A geopolymeric product formation can be done by evaluating the operational envelope for synthesizing the geopolymers, i.e., by evaluating the ternary diagram of SiO 2 , Na 2 O, and Al 2 O 3 (Fig. 5a), it was observed that all the samples produced in the present work were contained in the envelope synthesis of geopolymer described in the literature [46,47]. Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Similar chemical reactions also occur in Portland and calcium aluminate cement [9]. The presence of calcium plays an important role in accelerating the geopolymer pavement process [5,10] due to its ability to harden at room temperature [11][12].…”
Section: Introductionmentioning
confidence: 77%
“…However, the chemical processes behind the formation of geopolymers are not clearly understood. These processes can be simplified into three stages [5][6][7]. The first is the dissolution of silicate and aluminum elements from fly ash dust in an alkaline solution to produce aluminate and silicate species.…”
Section: Introductionmentioning
confidence: 99%
“…Although the microstructures of the AFS and AAS mortar specimens before corrosion were dense, apparently, they suffered more serious attacks by acidic solutions. For specimens immersed in acetic acid, the structure was porous, and some calcium acetate and SiO 2 appeared, indicating the dissolution of C-(A)-S-H gel, which had a long chain structure [32] and was vulnerable in the acidic environment. In addition, the structure of the AAS mortar was more porous than that of the AFS mortar.…”
Section: Microscopic Analysis Of Hardened Paste After Acid Corrosion ...mentioning
confidence: 99%